2020
DOI: 10.1002/ett.3881
|View full text |Cite
|
Sign up to set email alerts
|

Data dissemination for Internet of vehicle based on 5G communications: A survey

Abstract: With the increase of the number of connected vehicles on roads, the data dissemination within traditional network suffers from many limitations like high latency, a significant amount of dropped packets and network congestion. Therefore, the Internet of vehicles (IoV) has been designed as an emerging paradigm that combines the intelligent transportation system (ITS) with Internet of Things (IoT) technology. IoV allows vehicles to exchange data with its surroundings in order to enhance the traffic safety and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…Numerous emerging technological paradigms, such as Industry 4.0 [1]- [3], Internet of Things (IoT) [4]- [6], and self-driving vehicles [7]- [10], require reliable low-latency communication that is untethered from cables [11], [12]. Proponents of these new technological paradigms have often deferred the provisioning of these required reliable lowlatency wireless communication services to the 5th Gener-ation (5G) mobile communication standard developed by the Third Generation Partnership Project (3GPP) [13]- [15].…”
Section: A Motivation 1: New 5g Campus Network For Industrymentioning
confidence: 99%
“…Numerous emerging technological paradigms, such as Industry 4.0 [1]- [3], Internet of Things (IoT) [4]- [6], and self-driving vehicles [7]- [10], require reliable low-latency communication that is untethered from cables [11], [12]. Proponents of these new technological paradigms have often deferred the provisioning of these required reliable lowlatency wireless communication services to the 5th Gener-ation (5G) mobile communication standard developed by the Third Generation Partnership Project (3GPP) [13]- [15].…”
Section: A Motivation 1: New 5g Campus Network For Industrymentioning
confidence: 99%
“…Many researchers identified driver drowsiness through mobile, sensors, and few of them utilized cloud-based architecture in the domain of IoT-based computing. In practice, the traditional network suffered from many limitations [ 125 ], such as high latency, packets dropout, high-energy consumption, and network congestion due to increased computational demands by the connected vehicles. To develop such an intelligent transportation system (ITS), there is a dire need to use IoT-technology for developing comprehensive and hybrid DFD systems.…”
Section: Iot-based Architectures For Dfd Systemsmentioning
confidence: 99%
“…To develop such an intelligent transportation system (ITS), there is a dire need to use IoT-technology for developing comprehensive and hybrid DFD systems. Authors suggested Vehicular ad hoc Networks (VANETs) [ 125 , 126 , 127 , 128 , 129 ], technology that can be used to enhance cloud-based and wireless architecture to process complex and huge data processing for vehicles. As a result, the VANETs became the main and important part of ITS technology to increase traffic mobility and efficiency.…”
Section: Iot-based Architectures For Dfd Systemsmentioning
confidence: 99%
“…IoV is developed by integrating the intelligent transportation system (ITS) and the internet of things (IoT). IoV integrates with heterogeneous network 5G that composes different radio access networks [1]- [4]. In general, IoV vehicles employs IEEE 802.11p for processing which is reliable for periodic data transmission but still it is insufficient to serve spectrum usages.…”
Section: Introductionmentioning
confidence: 99%